Epistemology of Pesantren: A Comparative Study of Traditional and Modern Pesantren - Ahdar Muslim; Edo Alvizar Dayusman (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2025)
This research is motivated by the problem of dichotomy and epistemological dialectics between the traditional pesantren model (salafiyah) that is rooted in the authority of texts and personal transmission, and the modern pesantren (khalafiyah) that adopts modern general science and scientific methodology, in the context of the challenges of globalization and digitalization. This study uses a qualitative approach with a library research method on 40 sources consisting of reputable journal articles, canonical works of Islamic boarding schools, and national media reports. The results of the research are presented in four main findings: (1) Sources and Validity of Knowledge: traditional pesantren are theocentric with revelation and the yellow book as authoritative sources, while modern pesantren are dichotomistic-integrative by admitting empirical verification; (2) The Role of Scientific Methodology: modern methodologies play a role as a verification tool and an academic framework in contemporary Islamic boarding schools, even though they are accompanied by integration and Islamization efforts; (3) Knowledge Transmission: there is a hybridization between traditional transmission based on the yellow book with digital disruption and amplification; (4) Hegemony and Authority: the charismatic and centralistic kiai authority is transformed to be more rational and distributed in modern Islamic boarding schools. The conclusion of the study shows that even though they have different paradigms, both have adaptive capacity. The implementation of the research results recommends the development of a